2014
DOI: 10.1002/2013jg002585
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of stoichiometric ratios in the Mississippi River to hydrologic variability

Abstract: (2014), Sensitivity of stoichiometric ratios in the Mississippi River to hydrologic variability, J. Geophys. Res. Biogeosci., 119, 1049-1062, doi:10.1002 AbstractThe ratio of key elements such as nitrogen, phosphorus, and silica determines nutrient limitations that are important to regulating primary productivity and species composition in aquatic ecosystems. The flux of these nutrients in streams, as dissolved constituents or as particulate matter, is sensitive to variability in flow conditions. Most previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…This variation is due almost entirely to decreased DIN in dry years and seems to occur in all agricultural watersheds up to about 80% agricultural land use. This is similar to the results of Leong et al (2014) who analysed the statistical relationship between Si : DIN and water discharge in rivers draining many basins across the Mississippi River watershed. Their results suggested that high discharge could increase DIN : Si by about 4% across the basin.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This variation is due almost entirely to decreased DIN in dry years and seems to occur in all agricultural watersheds up to about 80% agricultural land use. This is similar to the results of Leong et al (2014) who analysed the statistical relationship between Si : DIN and water discharge in rivers draining many basins across the Mississippi River watershed. Their results suggested that high discharge could increase DIN : Si by about 4% across the basin.…”
Section: Discussionsupporting
confidence: 88%
“…This is similar to the results of Leong et al . () who analysed the statistical relationship between Si : DIN and water discharge in rivers draining many basins across the Mississippi River watershed. Their results suggested that high discharge could increase DIN : Si by about 4% across the basin.…”
Section: Discussionmentioning
confidence: 99%
“…S1. The general correspondence in results between this study and that of Leong et al () is due in part to the fact that both use the same nutrient load data from the U.S. Geological Survey. But the analytical approaches are quite different, which provides strengthened confidence in the conclusion that mass of nutrient loads and stoichiometry of nutrient loads respond differently to hydrological conditions.…”
Section: Discussionsupporting
confidence: 78%
“…S1). Leong et al () reported that, for both the Arkansas River and the Red River, DSi had a stronger nonlinear response to increasing discharge than did N. If DSi is more strongly affected by discharge than is N, then it would generate the inverse relationship between the N‐ICEP and discharge shown in Supporting Information Fig. S1.…”
Section: Discussionmentioning
confidence: 99%
“…The Mermentau and Vermilion Rivers also had lower DOC:TP, DOC:DIP, Si:TP, and Si:DIP ratios than the Calcasieu River. The differences in those ratios can influence primary production and the composition of plankton communities in these rivers, individually or in combination, as such influence was found by other researchers [40,41].…”
Section: Land Use Effects On Phosphorus Fluxessupporting
confidence: 58%